PENGARUH KETIADAAN ALAT RADIOLOGI MAGNETIC RESONANCE IMAGING (MRI) PADA BERBAGAI JENIS TERAPI DI RSUD SUMBAWA DITINJAU DARI ASPEK KLINIS - Sapta Dwi Rosadi; Slamet Mardiyanto Rahayu; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
This study aims to analyze the clinical impact of the absence of Magnetic Resonance Imaging (MRI) equipment on the implementation and effectiveness of various therapeutic interventions at RSUD Sumbawa. The research employed a descriptive-analytic approach to evaluate the influence of MRI unavailability on diagnostic accuracy, clinical decision-making, referral patterns, and the timeliness of therapeutic interventions across diverse medical conditions. The findings indicate that the lack of advanced imaging facilities results in increased reliance on alternative diagnostic modalities, potential delays in establishing definitive diagnoses, and modifications of therapeutic strategies to accommodate existing infrastructural limitations. The clinical impact of the absence of MRI is substantial and is directly experienced by healthcare professionals at RSUD Sumbawa, particularly in the context of managing complex cases and determining optimal treatment plans. Therefore, the provision of MRI facilities represents a strategic necessity to enhance the quality of healthcare services and improve patient clinical outcomes in regional hospitals.